Effect of composition and macropore percentage on mechanical and in vitro cell proliferation and differentiation properties of 3D printed HA/β-TCP scaffolds. Issue 68 (5th September 2017) - Zhao, Ningbo; Wang, Yanen; Qin, Lei; Guo, Zhengze; Li, Dehua
Abstract : HA/β-TCP scaffolds were fabricated by 3D printing and exhibited desirable biocompatibility in vitro . Abstract : Alveolar ridge restoration and augmentation is a challenge in dental implantology. 3D printing allows the manufacture of scaffolds with controlled complex structure and adjustable pore size and percentage. HA/β-TCP is the most commonly used ceramic in 3D printing for its ideal biocompatibility, osteoconductivity, biodegradability, and lack of risk from infection or rejection. However, the effect of composition and macropore percentage ( P macro ) on the mechanical and biological properties of 3D printed HA/β-TCP scaffolds is debatable. In this study, HA/β-TCP scaffolds with various compositions (weight ratio (wt%) of HA varied at 0, 20, 40, 60, 80 and 100%) and P macro (0%, 30% and 50%) were fabricated via 3D printing. The effect of composition and P macro on the scaffold was investigated. The results showed compressive strength (CS) values, elastic modulus, degradation and biocompatibility in vitro were significantly affected by both the composition and P macro, which exhibited an interactive effect. Biphasic calcium phosphate ceramics demonstrated higher CS values, elastic modulus, seeding efficiency, cell proliferation and differentiation capability compared to pure HA or pure β-TCP scaffolds. The degradation of scaffolds decreased as HA wt% increased or P macro decreased. In conclusion, scaffolds with HA wt% of 40% and P macro of 50% performed optimum cell proliferation, while scaffolds with HA wt% of 60% and P macro of 30% exhibited optimum osteogenic differentiation. The results provide some useful insights on applying 3D printed HA/β-TCP scaffolds for augmenting absorbed alveolar ridges.